Analisis Proses Rekrutmen dan Seleksi Karyawan di PT. Bumen Redja Abadi Magelang - Revanza Harviananda Hutama; Dian Marlina Verawati (CV ODIS, 2023)
Human Resources in an organisation are things that are firmly connected with the advancement of the organisation. In any case, there are still organisations in which poor people can accomplish the organisation's objectives without limit. Hence, it is essential to examine the enrollment and choice interaction. A decent enrollment and determination process can uphold the procurement of HR with excellent execution and quality. This study aimed to determine how the enrollment and determination interact with PT Bumen Redja Abadi Magelang representatives. In leading the review, analysts utilised fascinating subjective exploration with purposive testing. The outcomes showed that the enlistment cycle and choice interaction affected the presentation of workers of PT Bumen Redja Abadi Magelang. In completing the enrollment cycle, candidates are restricted and focused on the people who are domiciled in Magelang; this severely affects the nature of HR in the company. In the choice cycle, the norm of whether an individual passes in the determination at PT. Bumen Redja Abadi Magelang is the consequence of a mental test and the development of an interview with the organisation’s HRD.